Teachers’ and Students’ Evaluation towards Online Teaching and Learning in English Speaking Class during Covid-19 Pandemic - Truong, Trần Minh Nhật; Duong, Thị Kim Oanh (Journal of Technical Education Science, 2023)
The sudden closure of higher education institutions during the COVID-19 pandemic last two years in Vietnam has caused learners to experience problems in learn-ing English, particularly speaking skills. Learning speaking skills is crucial because it is the main mode of communication worldwide. Most learning institutions across the world have adopted e-learning since the Covid-19 lockdown implementation. Teachers and students require more time to adapt to virtual learning since the majority of them are not well familiarized with the new technologies to be used in the online speaking classes. Hence, this paper investigates teachers' and learners' evaluation concerning with teaching and learning in online English Speacking Classes. The paper will also examine the challenges encountered by teachers and learners during online class. The study used a structured questionnaire cov-ering teachers' and learners' perceptions of online teaching - learning at two engineering technology universities in Ho Chi Minh City, Vietnam. The empirical data were collected by distributing questionnaire to 20 English teachers and 100 students. Data analysis was done by use of simple statistical tools like mean and percentages. The findings reveals that the quality of teaching and learning English speaking skills in online classes is not high due to the lack of interaction between teachers and students; Technology skills and online learning skills of students are still limited. Besides, the article makes some suggestions to improve the quality of teaching and learning English speaking skills in online classes based on the survey results.